2020
DOI: 10.1016/j.jalgebra.2020.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Ulrich ideals and 2-AGL rings

Abstract: The notion of 2-almost Gorenstein local ring (2-AGL ring for short) is a generalization of the notion of almost Gorenstein local ring from the point of view of Sally modules of canonical ideals. In this paper, for further developments of the theory, we discuss three different topics on 2-AGL rings. The first one is to clarify the structure of minimal presentations of canonical ideals, and the second one is the study of the question of when certain fiber products, so called amalgamated duplications are 2-AGL ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…These rings generalize almost Gorenstein ones that are obtained when either n = 0, in which case the ring is Gorenstein, or n = 1. In particular, in [6] it is studied the case of the 2-AGL rings, that are closer to be almost Gorenstein, see also [11].…”
Section: Gas Numerical Semigroupsmentioning
confidence: 99%
See 1 more Smart Citation
“…These rings generalize almost Gorenstein ones that are obtained when either n = 0, in which case the ring is Gorenstein, or n = 1. In particular, in [6] it is studied the case of the 2-AGL rings, that are closer to be almost Gorenstein, see also [11].…”
Section: Gas Numerical Semigroupsmentioning
confidence: 99%
“…Indeed a ring is almost Gorenstein if and only if it is either 1-AGL or 0-AGL, with 0-AGL equivalent to be Gorenstein. In this respect 2-AGL rings are near to be almost Gorenstein and for this reason their properties have been deepened in [6,11]. In [6] it is also studied the numerical semigroup case, where 2-AGL numerical semigroups are close to be almost symmetric.…”
Section: Introductionmentioning
confidence: 99%
“…In a one-dimensional non-Gorenstein almost Gorenstein local ring, the only possible Ulrich ideal is the maximal ideal ([10, Theorem 2.14]). In [7] the authors explored the ubiquity of Ulrich ideals in a 2-AGL rings (one of the generalizations of Gorenstein local rings of dimension one), and showed that the existence of two-generated Ulrich ideals provides a rather strong restriction on the structure of the base local rings ( [7,Theorem 4.7]). Nevertheless, even for the one-dimensional Cohen-Macaulay local rings, in general we lack an explicit and physical list of Ulrich ideals contained inside those rings, which possibly prevents further developments of the study of Ulrich ideals.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even for the one-dimensional Cohen-Macaulay local rings, in general we lack an explicit and physical list of Ulrich ideals contained inside those rings, which possibly prevents further developments of the study of Ulrich ideals. In order to supply the lack, continuing the work [7], the present research particularly focus on and investigate the question of how many and how ample two-generated Ulrich ideals are contained in a given numerical semigroup ring, which is a prototype of Cohen-Macaulay local rings of dimension one. As we shall show in the following, although the task is rather tough and the statements of the results are seemingly complicated, we are able to describe all the Ulrich ideals in certain specific numerical semigroup rings.…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, every such ring is n-AGL for some n and Gorenstein rings correspond to the 0-AGL rings, whereas a ring is 1-AGL if and only if it is almost Gorenstein ring but not Gorenstein. Therefore, in this perspective 2-AGL rings are the ones closer to be almost Gorenstein and for this reason their properties have been more studied, see, e.g., [11]. In particular, the notion of 2-AGL gives a partial answer to a natural question that arise studying the endomorphism algebra B: can we characterize when it is almost Gorenstein?…”
Section: Introductionmentioning
confidence: 99%